2022
DOI: 10.1111/boer.12359
|View full text |Cite
|
Sign up to set email alerts
|

The impact of “Mass Entrepreneurship and Innovation” policy on SMEs’ innovation: Using quasi‐natural experiments

Abstract: This study presents an in‐depth investigation of the impact of “Mass Entrepreneurship and Innovation” (MEI) policy on small and medium‐sized enterprises’ (SMEs’) innovation using the propensity score matching–difference‐in‐difference method. The MEI policy's R&D subsidies are found to generate a positive effect on SMEs’ innovation. Although R&D subsidies have no significant impact on SMEs’ strategic innovation, they can promote substantial innovation and establish a solid microfoundation for China's high‐quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Cash can reasonably measure enterprises’ profitability. SMEs with rich cash flow are usually more inclined to invest in R&D activities (Zhao et al 2022 ); (4) debt-paying ability, indicated by the logarithm of asset-liability ratio ( LnDebt ); (5) proportion of fixed assets, measured by the proportion of fixed assets in total assets ( Fasset ); and (6) R&D investment, measured by the logarithm of companies’ R&D expenditure ( LnRD ). Generally, companies with highly liquid assets tend to invest more in enterprise R&D and produce more innovative results (Pham et al 2018 ); (7) The number of employees, which is the logarithm of the number of employees in the business ( LnEmployee ); (8) Inst , which is indicated by the shareholding ratio of institutional investors; (9) Largest , indicated by the shareholding ratio of the largest shareholder.…”
Section: Methodsmentioning
confidence: 99%
“…Cash can reasonably measure enterprises’ profitability. SMEs with rich cash flow are usually more inclined to invest in R&D activities (Zhao et al 2022 ); (4) debt-paying ability, indicated by the logarithm of asset-liability ratio ( LnDebt ); (5) proportion of fixed assets, measured by the proportion of fixed assets in total assets ( Fasset ); and (6) R&D investment, measured by the logarithm of companies’ R&D expenditure ( LnRD ). Generally, companies with highly liquid assets tend to invest more in enterprise R&D and produce more innovative results (Pham et al 2018 ); (7) The number of employees, which is the logarithm of the number of employees in the business ( LnEmployee ); (8) Inst , which is indicated by the shareholding ratio of institutional investors; (9) Largest , indicated by the shareholding ratio of the largest shareholder.…”
Section: Methodsmentioning
confidence: 99%
“…Second, regarding variable selection, this paper considered only fiscal technology expenditure as one mediator. Still, there are many other factors at work, such as the innovation and entrepreneurship policies, that have been verified to promote the technological innovation of small-and medium-sized enterprises [94], and technological innovation has always been the driving force of green transformation [12]. These factors are likely to play mediating roles in the process of innovation and entrepreneurship support policies promoting urban green transformation.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…As "Mass Entrepreneurship and Innovation" received policy support from the central policy maker, many local governments issued corresponding measures to stimulate regional innovation and entrepreneurship. The "Mass Entrepreneurship and Innovation" policy directly affects both the entrepreneurship and innovation levels of the economy (Zhao et al, 2022) and thus affects regional TFP. However, as we focus on how digital economy development affects regional TFP, it is interesting to discuss the moderating effect of the government's entrepreneurship and innovation policy support on the interaction between the digital economy and regional TFP.…”
Section: Thus We Propose Hypothesis 2bmentioning
confidence: 99%